Strengthening Agricultural Communities with Organic Rice Development Using the Jajar Legowo System - A. Besse Dahliana; A. Murniati; Fitriadi; Andi Rismayanti Fianda Sari; Islawati; Riskiyani; Darma; Hujemiati; Murni Djabar; Yusnan Suyuti DM; Jumardi (International Journal of Business and Applied Economics, 2023)
The implementation of the non-profit program "Strengthening Agricultural Communities with Organic Rice Development Using the Jajar Legowo System" has been ongoing since June 2023. The approach offered to address the problems of this activity is to synergize community empowerment programs implemented by universities, regions, and local actors. Lontara Government and Gapoktan. The results of implementing this non-profit program are: (a) The socialization of the Jajar-Legowo planting method was successfully carried out among farmers, (b) The enthusiasm of the residents during the socialization was not followed by the courage to apply it directly in their fields, only one of the partner farmers was willing to cover their area to be used as a place of proof.